Exploring Indonesian Students’ Socio-Affective Perceptions of CLIL (Content and Language Integrated Learning) in a Science Class - Sulistyowati, Titis; Hana, Mil’ul; Rosiana, Rosiana; Kurniati, Diah (Universitas Muria Kudus, 2025)
CLIL (Content and Language Integrated Learning) is an innovative teaching approach that combines content subject with language learning. It is essential to explore students' socio-affective perceptions of the implementation of this approach because these perceptions can influence their learning experience and outcome. This study aims to explore students’ socio-affective perceptions of 11th grade senior high school students at MAN 2 Kudus regarding the use of CLIL in science class. In this study, researchers used qualitative methods with open-ended questionnaires and semi-structured interviews. The participants were 27 students in the 11th grade of XI-5 at MAN 2 Kudus. The results show that students’ attitudes in CLIL-based Science class, such as confidence, comfort, motivation, and participation, are influenced by their English proficiency. Those with higher English proficiency tend to feel more confident, motivated, and participative in the classroom, while those with lower proficiency have more challenges and participate less. Despite these challenges, most students had a positive perception of the use of the CLIL approach. They believe that it helps enhance their English skills, significantly improving their vocabulary.